2004
DOI: 10.1016/j.hrtlng.2004.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of sudden death from Mycobacterium tuberculosis in a foreign-born worker at a resort hotel

Abstract: A 60 year-old man born in Central America died suddenly in the hallway of his residence on the grounds of a resort hotel where he worked as a dishwasher. The dishwashing station was in a large, poorly ventilated area where a substantial number of food service workers (cooks, wait staff, bus persons, dishwashers, supervisors, etc.) shared air space with the index patient. Several social contacts of the patient reported that he had been coughing for many months before his death. The County Department Of Health c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…In such a case, diagnosis may require postmortem imaging and autopsy, which may delay tuberculosis infection control of contact persons and result in spread of infection. In contrast, when tuberculosis can be identified as the cause of death, actions to prevent secondary tuberculosis infection can be taken rapidly . In the present case, diagnosis was distracted by the possibility of traumatic bleeding from the nostrils based on an interview with a family member that the patient may have hit her face hard when she fell and that this may have caused bleeding; however, in retrospect, this trace was the only evidence supporting tuberculous bleeding in the airway.…”
Section: Discussionmentioning
confidence: 66%
“…In such a case, diagnosis may require postmortem imaging and autopsy, which may delay tuberculosis infection control of contact persons and result in spread of infection. In contrast, when tuberculosis can be identified as the cause of death, actions to prevent secondary tuberculosis infection can be taken rapidly . In the present case, diagnosis was distracted by the possibility of traumatic bleeding from the nostrils based on an interview with a family member that the patient may have hit her face hard when she fell and that this may have caused bleeding; however, in retrospect, this trace was the only evidence supporting tuberculous bleeding in the airway.…”
Section: Discussionmentioning
confidence: 66%
“…The case of a 60-year-old immigrant worker in New York who died suddenly is a good illustration of this. Investigation into the cause of his death revealed that he had been coughing for months before his death, and that PTB was the cause of his death; in addition, he had infected a good number of his coworkers 8. In another study of SD in suspicious circumstances in two young subjects, the cause of death at postmortem was found to be tuberculosis 9.…”
Section: Discussionmentioning
confidence: 99%
“…A case of a 60-year-old man who died from TB with no previous history of TB is reported. 12 In another case a 25-year-old person died suddenly due to myocardial TB while playing soccer. 13 Pulmonary TB is treatable, but deaths due to its complications are on the rise due to its association with HIV infection and evolution of multi drug resistant tubercle bacilli strains.…”
Section: Discussionmentioning
confidence: 99%